Over a million students use our free study notes to help them with their homework
tan(3x)=tan(2x+x), by using the identity for tan(A+B)=(tan(A)+tan(B))/(1-tan(A)tan(B)),tan(3x)=tan(2x+x)=(tan(2x)+tan(x))/(1-tan(2x)tan(x)), using it again for tan(2x),tan(3x)=tan(2x+x)=([(tan(x)+tan(x))/...
equation of tangent is y - y1 = m(x-x1). differentiating y gives us the value of m. so dy/dx = 4x-10. we know x is 3. therefore, dy/dx = m = 2 but we need equation of the normal, which is y-y1=(1/m)(x-x1)...
Student should use a combination of trigonometric identities, product rule and chain rule to find dy/dx.This can be done by applying product rule, obtainingdy/dx = sin(2x). d[cos(x)^2]/dx + cos(x)^2. d[si...
I would convert the sin squared theta into a cos squared theta using identity that sin sq + cos sq = 1This would then give me a quadratic equation which I would substitute X = cos thetaThen I would solve ...
A)1) Draw a diagram of the circle displaying the centre and perimeter points along with their respective co-ordinates.2) Write down the equation for a circle labelling the centre and perimeter points. 3) ...
←
190
191
192
193
194
→
Internet Safety
Payment Security
Cyber
Essentials